Attentional biases in abstinent patients with cocaine use disorder: rapid orienting or delayed disengagement? - Branchadell, Victoria; Poy, Rosario; Segarra, Pilar; Ribes-Guardiola, Pablo; Moltó, Javier (Frontiers in Psychology, 2024)
Addiction-related attentional biases may play a central role in the development and maintenance of drug-seeking and drug-taking behaviors. However, evidence in cocaine dependence is limited and mixed. This study examined the time course and component processes of attentional biases for cocaine-related cues in a sample of 47 outpatients (38 men) with cocaine use disorder (CUD) with varying durations of current abstinence. Reaction times in a visual dot-probe task with two picture exposure durations —500 ms, to assess initial stages of attention, and 2,000 ms, to assess maintained attention— were recorded. We found faster responses to probes replacing cocaine-related vs. matched control pictures in the 500 ms but not in the 2,000 ms condition, indicative of early but not late attentional biases for cocaine cues in abstinent patients with CUD. Further comparisons with a neutral baseline revealed that it was not due to rapid orienting but to delayed disengagement from cocaine-related pictures, being this effect greater the longer the period of current abstinence. Consistent with the incentive-sensitization theory, these data suggest that cocaine-related stimuli maintain the capacity to hold spatial attention in abstinent patients with CUD, even after months of abstinence, highlighting the relevance of carrying out stimulus control to avoid relapses.